2016
DOI: 10.1111/capa.12176
|View full text |Cite
|
Sign up to set email alerts
|

From change to stability: Investigating Canada's Office of the Auditor General

Abstract: Through its audits and recommendations, Canada's Office of the Auditor General (OAG) has promoted financial probity and good governance for over a century. While OAG recommendations may have inherent value, their full value is realized only when implemented by government. By investigating implementation rates and the OAG's interaction with Parliament, this paper evaluates whether OAG performance and interactions with Parliament have changed over time.Sommaire : De par ses audits et ses recommandations, le Bure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Similarly, Taft (2016), in his review of the VfM audit over the last 20 years, finds that auditors' recommendations are gradually accepted by the bodies subject to auditing, reflecting the benefits added by the auditors' suggestions, while the results of Van Loacke and Put (2011) indicate that VfM audit allows public organizations to identify weaknesses in their own management. This contradicts Alwardat et al (2015), who found that the VfM audit is not as effective as previously believed, which made them call for further studies on the VfM audit and its implementation in the UK public sector organizations.…”
Section: Literature Review and The Vfm Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Taft (2016), in his review of the VfM audit over the last 20 years, finds that auditors' recommendations are gradually accepted by the bodies subject to auditing, reflecting the benefits added by the auditors' suggestions, while the results of Van Loacke and Put (2011) indicate that VfM audit allows public organizations to identify weaknesses in their own management. This contradicts Alwardat et al (2015), who found that the VfM audit is not as effective as previously believed, which made them call for further studies on the VfM audit and its implementation in the UK public sector organizations.…”
Section: Literature Review and The Vfm Conceptmentioning
confidence: 99%
“…Morin and Hazgui (2016) find that VfM audits enable public organizations to improve their governance. Similarly, Taft (2016), in his review of the VfM audit over the last 20 years, finds that auditors’ recommendations are gradually accepted by the bodies subject to auditing, reflecting the benefits added by the auditors’ suggestions, while the results of Van Loacke and Put (2011) indicate that VfM audit allows public organizations to identify weaknesses in their own management. This contradicts Alwardat et al.…”
Section: Literature Review and The Vfm Conceptmentioning
confidence: 99%
“…Morin's study confirmed findings in Scotland, as well as local governments in Finland and Norway, which revealed that VFM audits are regarded by the auditees as an important and efficient tool for controlling and reforming the public sector (Morin ; Lapsley and Pong ; Johnsen et al ). In the Canadian context Taft () concluded that recommendations by Auditors have been more frequently accepted and implemented over the past twenty years. Still, the assumption was that VFM audits rigorously covered all aspects of spending.…”
Section: Perspectives On Vfm Auditingmentioning
confidence: 99%
“…The general contents of government accounting have been examined (Liguori et al, 2018). Frequent topics of academic research also comprise other than content aspects of government performance auditing in individual countries (Guthrie and Parker, 1999;Dirsmith et al, 2000;English and Guthrie, 2000;Sampaio de Freitas and Aquino Guimarães, 2007;Grönlund et al, 2011;Raudla et al, 2016;Taft, 2016;McKevitt, 2017;Reichborn-Kjennerud and Johnsen, 2018). Moreover, government performance auditing in two or more countries has often been contrasted (Gray et al, 1993;Pollitt et al, 1999;Rist, 1999;Furubo et al, 2002;Norton and Murphy Smith, 2008;Torres et al, 2019;Jeppesen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We might have stayed strictly confident to the textual character of our examination, leaving it to other types of studies (Guthrie and Parker, 1999;Taft, 2016) to elaborate the preconditions for the changes in the empirical content patterns of the NAOF performance audits. However, we concluded that we will not compromise the characteristics of our study as a textual analysis even if we develop focused ex post fact interpretations of the preconditions indicated.…”
mentioning
confidence: 99%